Relations between shyness and assertiveness traits with the dimensions of the five-factor model - Bratko, Denis (Array, 2002)
Five-factor model (Costa & McCrae, 1992) represents comprehensive framework for organizing individual differences into five broad dimensions: Neuroticism, Extraversion, Openness to Experience, Agreeableness and Conscientiousness. Lower-level personality traits are expected to be correlated with these dimensions. The purpose of this study was to explore the relations among shyness, assertiveness and dimensions of the five-factor model. A sample of 336 high-school students (124 male and 212 female adolescents) completed the self-report version of the NEO Five Factor Inventory (NEO-FFI ; Costa & McCrae, 1992), as well as the Shyness and Assertiveness questionnaire (USA-97 ; Zarevski & Vukosav, 1999). Results revealed a complex pattern of relations between the five-factor personality model and shyness and assertiveness. The predictive power of the NEO-FFI dimensions was higher in the female sample than in the male sample for both shyness(R2females=0.37 : R2males=0.12) and assertiveness (R2females=0.36: R2 males=0.16).